Assessment of electrocoagulation based on nitrate removal, for treating and recycling the Saharan groundwater desalination reverse osmosis concentrate for a sustainable management of Albien resource. Issue 2 (April 2019) - Berkani, Ismahane; Belkacem, Mohamed; Trari, Mohamed; Lapicque, François; Bensadok, Kenza
Abstract: The present work is devoted to the salinity abatement of the groundwater desalination RO concentrate, and the study of its possible reuse. As NO3 − and some of its by-products represent the highest risk for the environnment, its removal has been studied to optimize some operating parameters. Firstly, to ensure sufficient solution conductivity and to avoid the inhibitory and interactions effect of other ions present in the concentrate, EC experiments were carried out with synthetic solutions containing only Cl − and SO4 2− ions. The results showed that at the optimal conditions (Al/Al, 100 A/m 2, pH 7 and 180 min), the NO3 − removal reached 93%. Secondly, to study their inhibitory effect on NO3 - removal, the coexisting ions (Cl −, SO4 2−, HCO3 −, K +, Mg 2+, Ca 2+, Na + and F − ) were added successively until obtaining a synthetic solution representing the real concentrate. The study showed that SO4 2−, HCO3 − and Ca 2+ ions are the main species that inhibit the NO3 − elimination. Otherwise, the mechanism showed that NO3 - was eliminated by both adsorption and chemical reduction to ammonium NH4 + . Also, no nitrite NO2 − and no ammonia NH3 were detected. Finally, optimal conditions applied to the synthetic and real RO concentrate, led to very significant decrease in ions concentration. In the case of the real RO concentrate, the ions abatement attained 62.00, 30.33, 42.49, 29.12, 83.23, 31.74, 27.59 and 69.20% respectively for NO3 -, Cl-, SO4 2-, K +, Mg 2+, Ca 2+, Na + and F-. As the final concentrations of all ions were close or less than to those contained in the raw groundwater, and to preserve the Albien resource, the treated concentrate could be recycled upstream of the RO process.